English Language Proficiency Skills Among High School Students: Basis for an Intervention Program - Edgar Rendon Eslit; Analiza Valderama (English Learning Innovation (englie), 2023)
Speaking proficiency has special value anywhere in the world. It needs to be possessed by every individual to bring change to society. This clenches the amplified direction of the current study, where its primary objective is to assess the speaking skills of the SHS-HUMMS students of the DNHS. This study envisioned identifying the speaking factors in terms of grammar, vocabulary, aspects of discourse, pronunciation, and interaction. It utilizes the quanticorrelational descriptive method, which uses the purposive sampling procedure. Standardized rubrics for speaking skills were utilized, tabulated, and interpreted using the appropriate tools. This was further validated by the concurrent opinions of two language experts in the area of linguistics. Overall, the findings revealed a speaking peculiarity in proficiency. This surfaced after the data were treated with statistical measures using frequency and percentage, Kruskal-Wallis H-value for pairwise comparison, ANOVA, and Shapiro-Wilk for multi-variant normality. This was explained using a contingency table. Furthermore, the results showed no significant difference between the levels of indicators affecting speaking skills. Two factors that affected the respondents’ speaking skills, however, were pronunciation and interaction. Overall, an intervention program was put in place in order to address the speaking problem of the respondents.